SCHOOL MANAGEMENT IN THE PANDEMIC CONTEXT: INSECURITIES, VULNERABILITIES, AND DECISION-MAKING PROCESSES - Pinto, Joane Vilela [UNESP]; Leite, Yoshie Ussami Ferrari [UNESP]; Teixeira, Leny Rodrigues Martins [UNESP]; Lima, Tamara de; Klebis, Augusta Boa Sorte Oliveira [UNESP]; Deak, Simone Conceicao Pereira [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2024)
The aim of this article is to investigate and understand the challenges faced by principals and educational coordinators during the COVID-19 pandemic. Initially, reflections are made on the role of school managers and working conditions in the pandemic context. Next, data from an online questionnaire administered to 66 managers is analyzed to find out about aspects related to health, activities carried out and the school-family relationship. By presenting a comprehensive view of the challenges and strategies adopted by managers, this qualitative research contributes to understanding the main difficulties faced by schools, teachers and students during the 2020/2021 pandemic. The results point to the need to implement policies that consider the specific needs of schools in a context marked by exceptional and unique circumstances. They also offer insights that can contribute to the formulation of policies and practices in times of crisis, as well as to future research.
Keywords: Basic education; Educational managers; COVID-19 Pandemic